Dissociations and similarities in motor intention and motor awareness: the case of anosognosia for hemiplegia and motor neglect. Issue 4 (6th September 2012) - Garbarini, Francesca; Piedimonte, Alessandro; Dotta, Manuela; Pia, Lorenzo; Berti, Anna
Abstract : Objectives: To confront motor awareness in anosognosia for hemiplegia (AHP), where paralyzed patients deny their motor impairment, and in motor neglect (MN), where non-paralyzed patients behave as if they were paretic. Methods: Eight right-brain-damaged-patients, 4 hemiplegic (2 with and 2 without AHP) and 4 non-hemiplegic (2 with only perceptual-neglect and 2 with also MN) were evaluated with a bimanual motor battery, before and after examiner's reinforcement to use the contralesional limb. The requested bimanual movements could be either symmetric or asymmetric, either intransitive or transitive (with/without objects). We compared the examiner's evaluation of patients' performance with the patients' self-evaluation of their own motor capability (explicit knowledge). We also evaluated the presence/absence of compensatory unimanual strategies that, if present, suggests implicit knowledge of the motor deficit. Results: We found significant differences between conditions only in MN patients, whose performance was better after the examiner's reinforcement than before it, during symmetric than asymmetric movements and during intransitive than transitive movements. As for motor awareness, we found a lack of explicit and implicit knowledge in both AHP and MN patients. Conclusion: Although different in terms of motor intention and motor planning, AHP and MN are both characterised by anosognosia for the motor impairment.